[Rezension von: Lo scioglimento del matrimonio in favorem fidei : a vent'anni dall'istruzione Potestas Ecclesiae (2001-2021) : norme e note] - Campos Martínez, Francisco José (Revista española de derecho canónico, 2023)
Recension of the book of the CONGREGATION FOR THE DOCTRINE OF THE FAITH.T he volume is part of the "Documenti e Studi" collection of the Department for the Doctrine of the Faith and is the result of the work carried out on the occasion of the Study Day, organized by said Department and by the Faculty of Canon Law of the Pontifical University Lateran, on April 27, 2021, under the title «The dissolution of marriage in favorem fidei. Twenty years after the Instruction Potestas Ecclesiae (2001-2021)».